2019
DOI: 10.1186/s13045-019-0727-4
|View full text |Cite
|
Sign up to set email alerts
|

Fludarabine-treosulfan compared to thiotepa-busulfan-fludarabine or FLAMSA as conditioning regimen for patients with primary refractory or relapsed acute myeloid leukemia: a study from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation (EBMT)

Abstract: Background Limited data is available to guide the choice of the conditioning regimen for patients with acute myeloid leukemia (AML) undergoing transplant with persistent disease. Methods We retrospectively compared outcome of fludarabine-treosulfan (FT), thiotepa-busulfan-fludarabine (TBF), and sequential fludarabine, intermediate dose Ara-C, amsacrine, total body irradiation/busulfan, cyclophosphamide (FLAMSA) conditioning in patients with refractory or relapsed AML. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…So far, allogeneic hematopoietic stem cell transplantation(allo-HSCT)remains the most effective way to cure refractory leukemia [1][2][3][4] and undergoing allo-HSCT promptly is essential for them. Recently, some studies showed that intensified conditioning followed by allo-HSCT could achieve acceptable outcomes for refractory leukemia [5][6][7][8][9]. In our transplant center, a strategy of sequential intensified conditioning followed by donor lymphocyte infusion (DLI) was implemented since 2009, and encouraging outcomes were reported previously [10].…”
Section: Introductionmentioning
confidence: 95%
“…So far, allogeneic hematopoietic stem cell transplantation(allo-HSCT)remains the most effective way to cure refractory leukemia [1][2][3][4] and undergoing allo-HSCT promptly is essential for them. Recently, some studies showed that intensified conditioning followed by allo-HSCT could achieve acceptable outcomes for refractory leukemia [5][6][7][8][9]. In our transplant center, a strategy of sequential intensified conditioning followed by donor lymphocyte infusion (DLI) was implemented since 2009, and encouraging outcomes were reported previously [10].…”
Section: Introductionmentioning
confidence: 95%
“…A total of eighteen articles underwent full-text review and 9 of them were excluded because they did not report the primary outcomes of interest. Finally, 12 studies fulfilled the eligibility criteria and were included in the meta-analysis [3,6,7,8,9,10,11,12,13,14,15,16]. A manual review of the bibliography of the included studies, and some selected review articles, did not yield any additional eligible studies.…”
Section: Resultsmentioning
confidence: 99%
“…The pooled 1-, 2- and 3-year OS rates were 59.6% (95% CI, 47.9–70.2%; I 2 94%; Figure 2A) [6,7,8,14,15,16], 48.4% (95% CI, 37.3–59.6%; I 2 96%; Figure 2B [3,6,8,10,13,14,15,16], and 40.2% (95% CI, 28.0–53.7%; I 2 96%; Figure 2C) [6,7,11,12,14,15,16], respectively. The pooled 1-, 2- and 3-year LFS were 57.4% (95% CI, 38.6–74.2%; I 2 98%; Figure 2D) [6,14,15,16], 49.4% (95% CI, 38.1–60.8%; I 2 95%; Figure 2E [3,6,9,13,14,15,16], and 39.3% (95% CI, 26.4–53.9%; I 2 97%; Figure 2F) [6,7,12,14,15,16], respectively. The pooled 2- and 3-year RR were 31.3% (95% CI, 21.1–43.8%; I 2 96%; Figure 3A) [3,6,10,13,14,15,16] and 41.9% (95% CI, 30.9–53.8%; I 2 95%; Figure 3B) [6,7,11,12,14,15,16], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations